2003
DOI: 10.2334/josnusd.45.111
|View full text |Cite
|
Sign up to set email alerts
|

Production of antibody against a synthetic peptide of Porphyromonas gingivalis 40-kDa outer membrane protein

Abstract: OriginalProduction of antibody against a synthetic peptide of Porphyromonas gingivalis 40-kDa outer membrane protein Abstract: Porphyromonas gingivalis has been implicated as a major pathogen in periodontal diseases. We previously cloned a 40-kDa outer membrane protein (OMP) gene from P. gingivalis 381 and succeeded in producing sufficient quantities of the recombinant protein for experimental use. Since antibodies against the recombinant (r) 40-kDa OMP have potent ability to kill P gingivalis cells by complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The results of this investigation indicated that patients with chronic periodontitis showed high serum levels of IgG against the soluble extract of P. gingivalis ATCC33277 while patients with gingivitis and periodontally healthy individuals presented a weak immunoreactivity to this antigen. This finding is in accordance with the outcomes of several studies, which have demonstrated higher antibody titers in subjects with periodontitis compared to healthy controls 4 , 6 , 14 , 16 .…”
Section: Discussionsupporting
confidence: 92%
“…The results of this investigation indicated that patients with chronic periodontitis showed high serum levels of IgG against the soluble extract of P. gingivalis ATCC33277 while patients with gingivitis and periodontally healthy individuals presented a weak immunoreactivity to this antigen. This finding is in accordance with the outcomes of several studies, which have demonstrated higher antibody titers in subjects with periodontitis compared to healthy controls 4 , 6 , 14 , 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Dot‐blot assays, along with the other techniques described in this article, provide useful information about the sensitivity of each particular mAb for viral antigens detection. As reported previously [Bhunia et al, ; Tsurumi et al, ], the dot‐blot technique can be considered as a valid, useful and affordable method to qualitatively study the antigen–antibody binding reaction. These studies showed that these mAbs are specific for the detection of the respective RSV protein tested.…”
Section: Discussionmentioning
confidence: 84%
“…The use of synthetic peptide immunogens as means to generate specific immunological reagents for a variety of purposes has increased markedly in recent years [17].…”
Section: Discussionmentioning
confidence: 99%